The Investigation of Total Quality Management in Health Care System (The Case of Hospital Employee in Libya Hospitals) - Almahashhash, Hind. Fathi. A. (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2018)
This study is targeted at investigating the application total quality management (TQM) within the hospitals and also seeks out the factors which are contribute to reaching the ideal total quality management. The research relied on exploratory factor analysis methodology. The surveys were distributed to different hospitals in Benghazi, Benghazi medical center, Al-hawari hospital, Al-Jalaa hospital, Ibn-Sina hospital, Al-Kawafia hospital. These are the main large hospitals, also the survey was distributed to three different polyclinics. The results of this study revealed poor application of the TQM concepts. Exploratory Factor Analysis (EFA) results demonstrated six factors which affect total quality management within Libyan hospitals. Besides, the people who are responsible for the health sector management should consider the Total Quality Management applied in small hospitals and polyclinics better than the others. The experience, system of work and education has an impact on Top Management Commitment and Patient Focus. The most implemented concepts were Internal Policy Knowledge and Teamwork within polyclinics, and the least implemented were Top Management Commitment and Patient Focus in the large hospitals. Keywords: Total Quality Management, Internal Policy Knowledge, Employee Engagement, Team Work, Training, Top Management Commitment and Patient Focus.

ÖZ Bu çalışma hastanelerde uygulanan toplam kalite yönetimini (TKY) araştırmayı ve ideal toplam kalite yönetimine katkıda bulunan faktörleri araştırmayı hedeflemektedir. Araştırma, araştırmacı faktör analizi metodolojisine dayanıyor. Anketler, Bingazi, Bingazi Tıbbı Merkezi, Al-Hawari Hastanesi, Al-Jalaa Hastanesi, İbni-Sina Hastanesi ve Al-Kawafia hastanelerine dağıtıldı. Bunlar büyük hastanelerdir ve bu anket hastanelerin üç farklı polikliniğine dağıtılmıştır. Bu çalışmanın sonuçları TKY kavramlarının zayıf bir şekilde uygulandığını ortaya koyarken, EFA sonuçları da Libya'daki hastanelerde toplam kalite yönetimini etkileyen altı faktörü ortaya koymuştur. Ayrıca, sağlık sektörü yönetiminden sorumlu kişiler, küçük hastanelerde ve polikliniklerde uygulanan Toplam Kalite Yönetimi'ni diğerlerinden daha iyi değerlendirmelidir. Deneyim, çalışma sistemi ve eğitim ise, Üst Yönetim Taahhüdü ve Hasta Odaklanma'da bir etkiye sahiptir. En çok uygulanan kavramlar, Polikliniklerde İç Politika Bilgisi ve Ekip çalışmasıyken, en az uygulananlar, büyük hastanelerde Üst Yönetim Taahhüdü ve Hasta Odaklanma olmuştur. Anahtar kelimeler: Toplam Kalite Yönetimi, İç Politika Bilgisi, Çalışan Katılımı, Takım Çalışması, Eğitim, Üst Yönetim Taahhüdü ve Hasta Odaklanma.
Master of Business Administration in Business Administration. Thesis (M.B.A.)--Eastern Mediterranean University, Faculty of Business and Economics, Dept. of Business Administration, 2018. Supervisor: Prof. Dr. Mustafa Tümer.
Keywords: Business Administration; Total Quality Management--Health Care System--Libya; Planning, policy making, control, quality management--Health Services--Hospitals--Libya; Medical policy--Libya; Hospitals--Administration--Libya; Total Quality Management; Internal Policy Knowledge; Employee Engagement; Team Work; Training; Top Management Commitment and Patient Focus